Plan de negocios, mediante la aplicación de la metodología de Canvas, para proponer la creación de las cabañas ecoturísticas "cabeceras del piatua", en el sector colonia, 4 de agosto del cantón Santa Clara - Velasco Moreta., Juan Miguel (2016)
The project is focused on making a business plan, by applying the methodology CANVAS, to propose the creation of ecotourism Cabins "headers Piatua" in the Cologne area, August 4 Canton Santa Clara, as identifies as problematic the lack of projects to enable community development, so that it complies with objectives such as making the situational analysis of the study area, to further develop a business plan, to propose the creation of ecotourism lodges, organizing a socialization of the research project in the sector; applying qualitative and quantitative methods allowed to obtain statistical data based on the application of surveys and implementation of cost accounting tables for local investment needed for implementation. On the other hand I said to be qualitative in view that the responses of tourists were analyzed and focused based on the methodology CANVAS allowed strategically develop the image, use of brand and marketing strategies in the business, it was obtained as results the design of the cabins to satisfy customers traveling in groups especially characterizations of domestic tourism, finally identifying the feasibility of the project based on the analysis of the internal rate of return, thus benefiting the community and all its members with the achievement of the objectives with the support of public institutions such as the Ministry of Tourism, Provincial and cantonal government.